Fermented Coconut Dregs Quality and Their Effects on the Performance of Broiler Chickens - Hafsah Hafsah; H. B. Damry; U. Hatta; B. Sundu (Tropical Animal Science Journal, 2020)
This study was conducted to determine the effects of the fermentation duration of coconut dregs (CD) by Saccharomyces cerevisiae and the addition of ammonium sulfate on the growth performance, feed digestibility, carcass, and digestive organ developments. A finely ground CD was autoclaved at 20 psi for 20 minutes and added distilled water to meet 80% moisture content. The autoclaved substrate was added with different concentrations of ammonium sulfate and fermented with Saccharomyces cerevisiae to produce Saccharomyces cerevisiae-fermented CD. A total of 192 day-old-unsexed Cobb broiler chicks were used and kept for 6 weeks. The birds were fed experimental diets ad-libitum. The experimental diets were produced by two durations of fermentation (5 days and 7 days) and three levels of ammonium sulfate (0%, 0.2%, and 0.4%) in 4 replicates. The experimental diets were offered ad-libitum and water were available at all times. Fermentation decreased lipid and crude fiber content of CD and the addition of ammonium sulfate increased protein content and amino acid concentration of CD. The bodyweight gain of birds increased when the CD was fermented for 5 days and with the addition of 0.2% ammonium sulfate. Dry matter digestibility and protein digestibility were improved when CD was added with 0.2% ammonium sulfate. In conclusion, fermenting CD for 5 days increased body weight gain and the addition of 0.2% ammonium sulfate improved the feeding value of the diet and growth of birds.